Valorization of Napier grass via intermediate pyrolysis: Optimization using response surface methodology and pyrolysis products characterization - Mohammed, I.Y. (Elsevier Ltd, 2017)
This study presents first optimization report on pyrolysis oil derived from Napier grass. Effects of temperature, heating rate and nitrogen flow rate on the intermediate pyrolysis of Napier grass biomass in a vertical fixed-bed tubular reactor were investigated collectively. Response surface methodology with central composite design was used for modelling the process and optimization of the process variables. Individual second order polynomial model was found to be adequate in predicting bio-oil, bio-char and non-condensable gas yield. The optimum bio-oil yield of 50.57 wt was recorded at 600 °C, 50 °C/min and 5 L/min nitrogen flow. The bio-oil obtained throughout this study was two-phase liquid, organic and aqueous phase. The bio-oil, bio-char and non-condensable gas were characterized using standard analytical techniques. The results revealed that the organic phase consists of hydrocarbons and various benzene derivatives, which can be further processed into fuels and valuable chemicals. The aqueous phase was predominantly water, acids, ketones, aldehydes and some phenolics and other water-soluble organics. The non-condensable gas was made up high hydrogen/carbon monoxide ratio suitable for liquid fuel synthesis via Fischer-Tropsch Synthesis. The bio-char was a porous carbonaceous material with high energy content, which can be applied as a solid fuel, adsorbent or source of biofertilizer. This study demonstrated that Napier grass biomass is a viable feedstock for production of high-value bioenergy precursors. © 2016 Elsevier Ltd